Hydrochemical characterization and assessment of groundwater quality from mining areas of Jakhaura Block, Lalitpur District, and remedial measures - Bisen, Utkarsh; Singh, S.P. (Journal of Degraded and Mining Lands Management, 2025)
The current study endeavored to assess the impact of mining on groundwater quality and to evaluate the hydrochemical characteristics of groundwater in the Jakhaura Block. In the present study, 28 samples were collected from different sites in the study area. pH, TDS, EC, Ca2+, Mg2+, K+, Na+, Cl-, SO42-, CO32-, HCO3-, F-, NO3- were determined. The BIS (2012) and WHO standards for drinking purposes were compared to estimate the deviation for the different parameters. The major cation concentration showed a trend of Ca2+>Na+>Mg2+>K+, and the major anion concentration showed the trend HCO3->Cl->CO32->SO42-. Piper trilinear plot and Chaddha diagrams suggest that the Ca-Mg-HCO3 recharging water type condition prevails in the major part of the area. In a few places, this is observed; the reverse ion exchange water type is also present. The Piper plot also suggests that most of the water is calcium bicarbonate type. Drinking, irrigation, and industrial suitability of groundwater were analysed using KR, SAR, and RSC, which suggest that groundwater is suitable for agriculture. Corrosivity Ratio (CR) calculated for Industrial suitability. Water Quality Index (WQI) was also calculated, which suggests deterioration of groundwater in the eastern region of the study area. At places Jakhaura in the north, Bansi in the East and Lalitpur in the South of the study area show very high values of WQI and require serious attention. A Research action plan was also discussed to overcome the effects of mining on the groundwater quality.